Tor-determining factors for the existence of a management risk committee in banking in Indonesia - Meilisa Anggraini (Institute of Accounting Research and Novation (IARN), 2021)
This study aims to identify the existence of a Risk Management Committee on banking in Indonesia. This Study uses the determinants of the existence of the Risk Management Committee which are independent commissioners, board size, auditor reputation, complexity and size of the company. The data used in this study is data banking on the Indonesia Stock Exchange (IDX) from 2009 to 2011. The sample collection used purposive sampling and resulted in 91 sample banks as a final sample. In this study using logistic regression analysis. The results of this study state that independent commissioner, board size, auditor reputation and complexity have no significant relationship with the existence of the Risk Management Committee. And the size of the company has a positive and significant relationship with the existence of a Risk Management Committee.